Motivation enhancement in a case of Alcohol dependence presented with Wernicke Encephalopathy: a Case Report - Shakya, Dhana Ratna; Yogi, Avash (Journal of Psychiatrists’ Association of Nepal, 2022)
Alcohol related complications are fairly common among the chronic users. Life threatening complication such as Wernicke encephalopathy does occur; we do encounter it as mental health professionals. Motivation to stop or change the drinking habit is very crucial in the management of cases of Alcohol use disorder. Such a condition with cognitive dysfunction in itself hinders the process in such a case. This case report highlights the implication of Wernicke encephalopathy (WE) and the process of motivation to change in such a case of Alcohol dependence syndrome (ADS). A 38-year-old case presented in our Emergency department with ADS, later upon shift to Psychiatry ward, Wernicke encephalopathy was also diagnosed. His initial assessment revealed confusion and his motivation in pre-contemplation stage. During the ward stay, as the patient condition stabilized with high dose of Thiamine and other measures, motivation enhancement was done. Later on, his motivation gradually changed to decision phase. Patient, since then, has been abstinent in alcohol